On the ethics of public nudging: Autonomy and agency - Christian Schubert (Ausschuss Wirtschaftswissenschaft und Ethik im Verein für Socialpolitik, 2016)
Nudges, i.e., low-cost interventions that steer people's behavior without compromising their freedom of choice, are the key contribution of 'Libertarian Paternalism' (LP) to public policy. They typically work through either harnessing or responding to people's cognitive biases and heuristics - which is why they have been criticized for being manipulative and for compromising personal autonomy. We argue, though, that (i) nudging hardly compromises autonomy, properly understood, and that (ii) it rather risks undermining people's agency, i.e., their ability to engage in creative self-constitution over time. This reorientation has far-ranging implications for the ethics of behavioral policies in general and LP in particular.
Keywords: 330; Social Marketing; Ethik